Cyborgs dan Perempuan Menurut Pandangan Posthumanisme Donna J. Haraway - Bagas Dwika Putra; Radea Yuli Ahmad Hambali (Jurnal Penelitian Ilmu Ushuluddin, 2023)
There is a need to re-question the human condition today, and technology changes the history of human civilization and social development, so that the "condition" of Posthumanism and cyborgs is one of them. The vision of 'post-gender' cyborgs has sparked feminist interest in reclaiming technology as a tool of liberation, whose identity has always been biologically identical, but cyborgs view this differently. Because of cyborgs, women are able to create their own identity, and create a more ideal reality for women. This research uses qualitative methods and literature study approach. The data used in this study are primary data in the form of the work of Donna J. Haraway and secondary data in the form of books and journals related to the discussion of this research. The conclusion of this study is that women should use technology as a tool for liberation and as a "former" of non-biological identity.